Alcohol Craving and Consumption in Borderline Personality Disorder: When, Where, and with Whom - Lane, Sean P. (Clin Psychol Sci, 2016)
Substance use is highly prevalent in our society, and substance use disorders are comorbid with most psychiatric disorders, including borderline personality disorder (BPD; Grant et al., 2006, 2008). Craving is a fundamental feature of addiction and disorder, yet the contexts in which craving occurs and is associated with substance use is still under-researched. We examined alcohol craving and consumption in a sample of 56 BPD individuals and a comparison group of community drinkers (COM; n = 60) who carried electronic diaries for approximately 21 days. BPD individuals reported more craving than COM individuals in most contexts. Compared to COM individuals, elevated craving in BPD individuals was paralleled by more drinking when at work, at home, and with romantic partners, coworkers, and children. These findings identify contexts of particular relevance to those with BPD and other mood/anxiety disorders in which craving may lead to risky and maladaptive alcohol use.